The Current State of Urological Education for Medical Students. Issue 1 (January 2017) - Kan, Kathleen M.; Jayadevan, Rajiv; Rodriguez, Nermarie; Weissbart, Steven; Stock, Jeffrey A.
Abstract : Introduction: : Providing medical students with a basic urological education is important as the geriatric population expands and the need for urological care increases. In the last decades there have been considerable changes to medical school curricula and graduation requirements that may impact medical student exposure to urology. We reviewed the literature pertaining to urological education for medical students in the United States. Methods: : We searched the PubMed® and Medline® databases to identify articles pertaining to medical student education in urology. We summarized these articles according to 4 themes, including 1) medical student electives in urology, 2) medical student career interest in urology, 3) new interventions in urology education and 4) the urology match. Results: : We identified 25 articles, which showed that 1) medical student exposure to urology has markedly declined, 2) medical students remain highly interested in pursuing a career in urology, 3) the AUA (American Urological Association) medical student curriculum has provided a key resource for medical school urological education and 4) applying for urology residency may be expensive and challenging. Conclusions: : Medical school urological education has changed in the last decades. Although it appears that fewer medical students are required to rotate through urology, new materials are available to educate medical students in urology and many students are highly interested in pursing a career in the field.